Une amitié passionnée: Clara Schumann - Brahms - Alley, Marguerite; Alley, Jean (Paris Laffont, 1955)
Correspondence between Clara Schumann and Brahms, 1854-1896.
Keywords: Music history; Composer; Correspondence